2016
DOI: 10.5807/kjohn.2016.25.4.300
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Psychosocial Work Conditions on Self-rated Health among Korean Workers

Abstract: Purpose: Few studies have considered the psychosocial work environment factors in relation to employee health. This study explored the relationship between psychosocial work characteristics and self-rated health among Korean employees. Methods: The study population of 21,476 employees was derived from the 2014 Korean Work Environment Survey (KWES). Psychosocial work environment was measured by Copenhagen psychosocial questionnaire scales. Results: Among employees at workplaces (n=21,476), 23.3% rated their hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…In total, 23% of the participants rated their health as poor. This finding is similar to the results (24.1%) of a previous survey conducted in 2018 (15), and it did not demonstrate a considerable difference from the poor SRH (23.3%) of native Korean wage workers in a previous survey (n = 21,476) (25). Numerous studies have reported that migrant workers have lower health statuses than the native population (26).…”
Section: Discussionsupporting
confidence: 89%
“…In total, 23% of the participants rated their health as poor. This finding is similar to the results (24.1%) of a previous survey conducted in 2018 (15), and it did not demonstrate a considerable difference from the poor SRH (23.3%) of native Korean wage workers in a previous survey (n = 21,476) (25). Numerous studies have reported that migrant workers have lower health statuses than the native population (26).…”
Section: Discussionsupporting
confidence: 89%
“…It is often considered natural for emotional laborers to be exposed to workplace violence in the Korean society [12], so it is necessary to examine the health impact of both factors together. Thus, in contrast to most previous studies that only utilized data from a single year [20,21], this study utilized data about workers' individual factors, working conditions, and psychosocial work environment from the third and fourth Korean Working Conditions Surveys (KWCSs) to investigate the impact of emotional labor and workplace violence.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective health impact and working environment satisfaction were also found to be factors affecting work-related health problems. Subjective health status is an indicator of the overall health level [20], and reliability has been secured through many studies and is used for health evaluation [21]. The finding that the probability of experiencing workrelated health problems is twice as high in the case of negative impacts suggests the need to further study factors affecting the subjective health impact in the electronics industry.…”
Section: Discussionmentioning
confidence: 99%